La relación entre la gestión financiera y la rentabilidad de la caja municipal de ahorro y crédito de Maynas, durante el periodo 2022 - Grandez Gonzales, Jorge Mesias (2024)
This study investigated the relationship between financial management and the profitability of Caja Maynas during the year 2022. A quantitative approach was used and monthly financial data was analyzed. The results showed a positive relationship between financial management and the profitability of the institution. Efficiency in financial management, measured through indicators such as the ratio of loans per employee and the ratio of loans per branch, was associated with higher profitability in terms of EBITDA and liquidity ratio. These findings support the reviewed background that highlights the importance of effective financial management to improve profitability in different business sectors. Recommendations were made to improve the efficiency of financial management, including optimizing credit allocation, improving liquidity management, and adopting innovative financial technologies. These recommendations are intended to strengthen the position of Caja Maynas in the Peruvian financial system and ensure sound and sustainable financial management in the future.